(alpha + gamma(1)) Complex phase formation in the Cu-10 mass% Al-6mass% Ag alloy - Adorno, A. T. [UNESP]; Silva, R. A. G. [UNESP]; Carvalho, T. M. [UNESP] (Springer, 2009)
In this work the (alpha + gamma(1)) complex phase formation reaction in the Cu-10mass% Al-6mass% Ag alloy was studied using Differential Scanning Calorimetry (DSC), Differential Thermodilatometry (DTD), X-ray diffractometry (XRD), Optical (OM) and Scanning Electron Microscopies (SEM). The results indicated the presence of two different processes, related to a change in the Ag diffusion route from the alpha matrix to the (alpha + gamma(1)) complex phase.
Keywords: Martensite; Cu-Al-Ag alloys; Thermodilatometry; Non-isothermal kinetics